Avenues of the membrane transport system in adaptation of plants to abiotic stresses. (3rd October 2019) - Vishwakarma, Kanchan; Mishra, Mitali; Patil, Gunvant; Mulkey, Steven; Ramawat, Naleeni; Pratap Singh, Vijay; Deshmukh, Rupesh; Kumar Tripathi, Durgesh; Nguyen, Henry T.; Sharma, Shivesh
Abstract: Abiotic stress imposed by many factors such as: extreme water regimes, adverse temperatures, salinity, and heavy metal contamination result in severe crop yield losses worldwide. Plants must be able to quickly respond to these stresses in order to adapt to their growing conditions and minimize metabolic losses. In this context, transporter proteins play a vital role in regulating stress response mechanisms by facilitating movement of a variety of molecules and ions across the plasma membrane in order to maintain fundamental cellular processes such as ion homeostasis, osmotic adjustment, signal transduction, and detoxification. Aquaporins play a crucial role in alleviating abiotic stress by transporting water and other small molecules to maintain cellular homeostasis. Similarly, other transporter families such as CDF, ZIP, ABC, NHX, HKT, SWEETs, TMTs, and ion channels also contribute to abiotic stress tolerance. Hormones and other signaling molecules are necessary to coordinate responses across different tissues and to precisely regulate molecular trafficking. The present review highlights the current understanding of how membrane transporters orchestrate stress responses in plants. It also provides insights about the importance of these sensing and adaptive mechanisms for ensuring improved sustainable crop production during unfavorable conditions. Finally, this review discusses future prospects for the use of computational tools in constructing signaling networks to improve our understanding of the behavior of transporters under abiotic stress.